Family intimacy and adolescent peer relationships: investigating the mediating role of psychological capital and the moderating role of self-identity - Zhou, Xin; Huang, Jin; Qin, Sushu; Tao, Kangsheng; Ning, Yumei (Frontiers in Psychology, 2023)
According to existing research, family intimacy affects the formation of peer relationships among adolescents; Parent-child relationships may influence children's relationships with peers, but the mechanism of its influence is still unclear due to the uncertainty of its effect. According to the ecological systems theory, this study examines how family intimacy affects adolescent peer relationships through psychological capital and how self-identity moderates this effect. These hypotheses were tested based on a survey of 414 adolescents, which showed that family intimacy positively affects adolescent peer relationships; Psychological capital plays a mediating role between family intimacy and adolescent peer relationships; Self-identity positively moderates the direct effects of family intimacy and adolescent peer relationships; Self-identity not only positively moderates the direct effect of psychological capital and adolescent peer relationship, but also positively moderates the indirect effect of family intimacy on adolescent peer relationship through psychological capital. This study provides new perspectives on the relevant mechanism of family intimacy and adolescent peer relationships.